Bedsores successfully treated with topical phenytoin - Inchingolo, Francesco; Vermesan, Dino; Inchingolo, Alessio D.; Malcangi, Giuseppina; Santacroce, Luigi; Scacco, Salvatore; Benagiano, Vincenzo; Girolamo, Francesco; Cagiano, Raffaele; Caprio, Monica; Longo, Lucia; Abbianante, Antonia; et al. (Acta Biomedica Atenei Parmensis, 2017)
Phenytoin is normally used in epilepsy treatment. One of the side effect affecting a significative part of the treated patients is the gingival overgrowth. It could surely be a correlation between this stimulatory effect and the assessment of phenytoin in wound healing. In fact, some studies of the literature have shown that topical phenytoin promotes healing of traumatic wounds, burns and ulcers by decubitus or stasis (diabetic or venous) and we emphasize, in vitiligo, a particular attention into repigmentation. The related mechanism of action seems to be multifactorial. In the present paper topical phenytoin has been used as wound-healing agent in 19 documented cases of bedsores, divided in treated and placebo group. The used concentration of phenytoin was 5 mg/L dissolved in a water solution of 9 g NaCl /L (0.9% P/V of NaCl). Patches soaked with phenytoin solution were applied over the bedsores along 3 hours every 12 hours. Results showed that phenytoin treated patients healed their wounds significantly before (p<0.001) with respect to controls.